Vitamin D receptor absence does not enhance intestinal tumorigenesis in ApcPirc/+rats - Amy A. Irving; Bayley J. Waters; Jeremy R. Seeman; Lori A. Plum; Hector F. DeLuca (Biology Open, 2022)
Epidemiological observations have prompted some to posit that elevated circulating vitamin D is responsible for reduced colon cancer in individuals residing near the equator. We have previously demonstrated that vitamin D has no effect on colon cancer in two rodent models of intestinal tumorigenesis. We have now extended this line of inquiry to ask whether ablation of vitamin D receptor (VDR) affects tumorigenesis. A VDR null rat was developed using Cas9-CRISPR technology, which allowed us to investigate whether 1,25(OH)D3 signaling through its receptor plays a role in intestinal tumorigenesis. Loss of VDR expression alone did not induce tumorigenesis, even in animals exposed to the inflammatory agent dextran sodium sulfate. These VDR−/− rats were then crossed with ApcPirc/+ rats, which are predisposed to the development of intestinal neoplasms. In combination with the Pirc/+ mutation, VDR loss did not enhance tumor multiplicity, growth, or progression in the colon or small intestine. This study demonstrates that the vitamin D receptor does not impact tumor development, and strongly supports previous findings that vitamin D itself does not play a role in colon cancer development or progression. Alternative explanations are needed for the original latitude hypothesis, as well as observational data in humans. This article has an associated First Person interview with the first author of the paper.